PENGARUH PRODUK, HARGA, PROMOSI, SALURAN DISTRIBUSI, DAN PROSES TERHADAP KEPUTUSAN BRAND SWITCHING PADA KARTU TELEPON SELULER - Adzim, Faudzul (Manajemen Bisnis, 2014)
The research purposes are to analyses the effect of product, price, promotion, place, and process on brand switching decisions, and to determine dominant effect of those on brand switching decisions. Logistic regression of analysis was used as statistical analyses. The result showed that product, price, promotion, place, and process have a positive effect on brand switching decisions. Variable process has a dominant effect on brand switching decisions. The suggestions from this resesarch that the company should have many efforts to provide guarantee to satisfied customers by offering qualified product, giving gift or bonuses and decreasing the mobile card price. Keyword: Product, Price, Promotion, Place, Process, Brand Switching, Mobile Card.